Artificial intelligence and human nature: Consciousness the final frontier and humanity’s cosmic footprint - Pieterse, Dr Andre (Stellenbosch Theological Journal, 2025)
Artificial intelligence transcends the borders between disciplines, and it is a vital component of current and future space exploration. Its applications surpass mere technical issues and the question regarding its ability to obtain consciousness needs to be resolved. The true nature of AI and the essence of humanity is at stake. The author proposes that true consciousness derives from God’s act of bestowing an awareness of the self, a mindfulness of the triune God as depicted in the narrative of Genesis 2 verse 7. The paper’s premise is that AI systems or robots could never lay claim to this unique encounter, and that true consciousness will forever be a bridge too far. A dominant feature of humanity’s scientific evolution in the last decades is the shallow base from which it originates and the inability to comprehend where novelty fits into the bigger picture. The author argues that the current hype about AI may fall prey to this dilemma. There is a growing need to connect the dots between the spiritual and the physical, between theology and natural science. Human beings leave cosmic footprints. It is our legacy and responsibility as imagers of the cosmic Christ, and the question about AI’s role in this process needs to be addressed.